Hacking offences or illegal Access to computer system - Elías Puelles, Ricardo Nicanor (2023)
In this article, the author examines the crime of illegal access to computer systems. To do so, he highlights the increase in reports over the last five years, analyzes the legislative proposal outlined in the Convention on Cybercrime, and reviews the legal formulas adopted by Latin American states that have adhered to the Convention. Then, the author conducts a historical study of computer intrusion crimes in Peruvian criminal legislation and analyzes different issues that arise in the current wording, concluding this section with a proposal for lege ferenda.In the second part, the author notes that hackers are equated with cybercriminals, which creates prejudices or stigmas towards this community and biases in criminal investigations, which could, in turn, lead to erroneous judicial decisions.